Management of Implementing Clean and Healthy Living Behaviorin Households in Manisa Village - Megasari, Anis Laela; Hardianti, Hardianti; Hilal, Achmad; Betan, Abu Bakar; Yanti, Penti Dora; Wiranti, Bhakti (International Journal of Health Sciences, 2024)
The current policy that regulates clean and healthy living behavior is the Republic of Indonesia Minister of Health Regulation Number 2269/Menkes/Per/XI/2011 concerning guidelines for fostering clean and healthy living behavior. Clean and healthy living behavior is a government priority program through community health centers and is an output target in implementing health development. The lowest coverage of healthy households in the Manisa Health Center Working Area is in the existing Manisa Village. The aim of the research is to determine the management of implementing clean and healthy living behavior in the household setting. This type of research is qualitative research. The informants for this research, managers of the community health center's clean and healthy living behavior program, community health center leaders, cadres, community leaders, religious leaders and the public, were taken using purposive sampling. Data collection was carried out through in-depth interviews, documentation review and Focus Group Discussions. The results of the research showed problems with the input component, the health promotion staff at the community health center had never received training, the funding allocation was very small, and the supporting facilities for Promkes were limited to print media. In the process, planning has not been implemented in an integrated manner, the organization and implementation of health promotions has not been carried out optimally, and monitoring is only based on the results of surveys of household clean and healthy living behavior. It is known that the output component of implementing clean and healthy living behavior in household management is still below the target. Implementation of management of clean and healthy living behavior in household arrangements is not as expected. Therefore, it is necessary to improve the quality of implementing staff, allocate funds and infrastructure, as well as improve management in implementing clean and healthy living behavior in the household structure.